2008
DOI: 10.1159/000185641
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results and Nutritional Consequences of Biliopancreatic Diversion: Three Years of Follow-Up

Abstract: Background: Bariatric surgery is the most effective long-term treatment for morbid obesity, reducing obesity-associated comorbidities. The aim of our work was to describe clinical results and nutritional complications in morbidly obese patients with biliopancreatic diversion. Methods: We have analyzed a consecutive series of 64 patients who have been followed up for 3 years after undergoing open biliopancreatic diversion by the Scopinaro technique. Results: Initial excess weight loss was 29.3% at 6 months and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 47 publications
1
42
1
3
Order By: Relevance
“…Weight loss changes uric acid metabolism by increasing renal clearance [39]. The observed long-term improvement and markedly lowered uric acid over 3 years after BPD-DS in the present study are more pronounced than earlier data report after BPD without DS [40].…”
Section: Follow-upcontrasting
confidence: 54%
“…Weight loss changes uric acid metabolism by increasing renal clearance [39]. The observed long-term improvement and markedly lowered uric acid over 3 years after BPD-DS in the present study are more pronounced than earlier data report after BPD without DS [40].…”
Section: Follow-upcontrasting
confidence: 54%
“…Furthermore, intramuscular supplementation in an oily depot form may lead to VitD levels being better sustained over time. In fact, some studies of BPD patients have shown low VitD levels [7,8,17] and high PTH levels [7,8,[17][18][19] approximately 1-4 years following surgery despite VitD oral supplementation, whereas one study found that the VitD deficiency and PTH elevation post-BPD was resolved in the majority of patients using oral supplements [20]. Also, Marceau et al [7] found that, in a study of 33 BPD patients, one-third of study participants self-reported non-compliance with oral VitD and calcium supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing numbers of this procedure are performed worldwide [3]. Many nutritional deficiencies especially trace element deficiencies have been reported postoperatively in patients undergoing obesity surgeries [4,5]. Trace elements play an essential role in biochemical processes supporting life such as cellular respiration, cellular utilization of oxygen, DNA and RNA reproduction, maintenance of cell membrane integrity, and sequestration of free radicals [6].…”
Section: Introductionmentioning
confidence: 99%